Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300623
|View full text |Cite
|
Sign up to set email alerts
|

Frame Analysis of Voice Interaction Gameplay

Abstract: Voice control is an increasingly common feature of digital games, but the experience of playing with voice control is often hampered by feelings of embarrassment and dissonance. Past research has recognised these tensions, but has not offered a general model of how they arise and how players respond to them. In this study, we use Erving Goffman's frame analysis [16], as adapted to the study of games by Conway and Trevillian [9], to understand the social experience of playing games by voice. Based on 24 intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Our participants mentioned that they felt less in control when using the voice assistant. This is consistent with prior studies that have found voice interaction to be associated with a lower subjective sense of control in both smart-home interfaces [45] and digital games [2]. We propose three features to reduce this perceived lack of control.…”
Section: Developing Voice-based Crowdsourcing Platformssupporting
confidence: 91%
See 1 more Smart Citation
“…Our participants mentioned that they felt less in control when using the voice assistant. This is consistent with prior studies that have found voice interaction to be associated with a lower subjective sense of control in both smart-home interfaces [45] and digital games [2]. We propose three features to reduce this perceived lack of control.…”
Section: Developing Voice-based Crowdsourcing Platformssupporting
confidence: 91%
“…Several studies have compared voice input to manual input for the same task and report that voice input rates well on engagement, but poorly on usability and sense of control [2,45]. Due to a lack of typical user interaction signals like mouse clicks and scroll movements, measuring and evaluating user satisfaction on voice interfaces greatly differs from traditional screen based interfaces.…”
Section: Related Work Voice Interaction and Digital Voice Assistantsmentioning
confidence: 99%
“…Goffman (1961) used games as an early example for frame analysis. Subsequently, frame analysis has been utilized in understanding the gameplay as social situation (Fine 1983), and in general to make sense of games and play (e.g., Allison et al 2019; Conway and Trevillian 2015; Mayer, Warmelink, and Zhou 2016; Mortensen 2011; Stenros 2010). However, frame analysis has been much less used to examine game design choices or games as media communicating certain framings.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study shows that in-game voice commands are associated with a sense of taking on a character in the game's world. The researchers believe that voice interactions that are conflicting with the social world can impede the player's engagement with the in-game world[3].…”
mentioning
confidence: 99%